2021
DOI: 10.3390/ijms22137230
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Ethanolic Extract from Rhizome of Polygoni avicularis against Renal Fibrosis and Inflammation in a Diabetic Nephropathy Model

Abstract: Progressive diabetic nephropathy (DN) in diabetes leads to major morbidity and mortality. The major pathological alterations of DN include mesangial expansion, extracellular matrix alterations, tubulointerstitial fibrosis, and glomerular sclerosis. Polygoni avicularis is widely used in traditional oriental medicine and has long been used as a diuretic, astringent, insecticide and antihypertensive. However, to the best of the authors’ knowledge, the effects of the ethanolic extract from rhizome of Polygoni avic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…There have been over 18,000 DN-related manuscripts published since the beginning of the 21 st century corresponding to a diverse array of topics including DN-related drug therapy [ 24 26 ], the pathology and pathophysiology of DN [ 27 ], the diagnosis of DN [ 28 , 29 ], the etiology of DN [ 30 , 31 ], and the epidemiology of DN [ 32 , 33 ]. Given the complexity and density of information published in this field over the past two decades, there is a clear need for a systematic and objective approach to surveying DN-related research directions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been over 18,000 DN-related manuscripts published since the beginning of the 21 st century corresponding to a diverse array of topics including DN-related drug therapy [ 24 26 ], the pathology and pathophysiology of DN [ 27 ], the diagnosis of DN [ 28 , 29 ], the etiology of DN [ 30 , 31 ], and the epidemiology of DN [ 32 , 33 ]. Given the complexity and density of information published in this field over the past two decades, there is a clear need for a systematic and objective approach to surveying DN-related research directions.…”
Section: Discussionmentioning
confidence: 99%
“…During the period from 2016 to 2021, the results of both biclustering analyses and SNAs indicated that plant extract-based drugs and sodium-glucose cotransporter-2 (SGLT2) inhibitors have emerged as promising directions for the drug-based treatment of DN. The Polygonaceae-derived Polygonum aviculare L. (PA) extract, for example, has been reported to alleviate DN through the amelioration of renal tubular fibrosis and glomerulosclerosis [ 26 ]. Ranunculus ternatus Thunb (RTT) was shown to suppress fibrotic and inflammatory responses, thereby protecting against DN-related pathogenesis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several evidences have shown that TGF- β is an important mediator of diabetic nephropathy. In rodent diabetes models, the levels of TGF- β 1 mRNA and protein in the glomeruli and renal tubules are increased [ 32 , 33 ]. In the TGF- β /Smad signaling pathway, TGF- β binds to the T β RII receptor and phosphorylates it and then forms a TGF- β complex by binding to T β RІ receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Among the pathological changes of diabetic nephropathy, glomerulosclerosis, tubular inflammation, tubular atrophy, and inter-tubular fibrosis are common (3). Renal fibrosis seen in diabetic nephropathy may damage tissue and thus organ function and finally lead to kidney failure (4,5). Renal fibrosis is associated with transforming growth factor β (TGFβ) / suppressor of mothers against decapentaplegic (Smad) signaling.…”
Section: Introductionmentioning
confidence: 99%